THE ROLE OF PRODUCTIVE UTILIZATION OF ZAKAT ON THE WELFARE OF MUSTAHIK - Ningsih, Sri Ratna; Fauziah Balgis, Lilis (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
This research aims to ascertain the impact of productive zakat utilization on the well-being of mustahik program recipients in the Zona Madina Dompet Dhuafa. The research methodology employed was quantitative, with a descriptive approach. The sampling technique employed was that of saturated sampling. In saturated sampling, members of the population are used as samples. A total of 55 respondents were included in the study. The data analysis technique employs the BAZNAS Welfare Index, a composite of CIBEST analysis, HDI modification, and independence index. The results of this research demonstrate that the utilization of productive zakat has a positive impact on the level of welfare of mustahik, as evidenced by the CIBEST analysis value of 0.96, which places it in the "good" category, the HDI modification value of 0.35, which places it in the "poor" category, and the independence index value of 0.74, which places it in the "good" category. It was subsequently determined that the BAZNAS Welfare Index value was 0.66, classified as belonging to the "good" category.